FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN JASA ANGKUTAN KERETA API PADA MASA PANDEMI COVID-19 DI STASIUN BATURAJA KABUPATEN OGAN KOMERING ULU - Eko Aprian Saputra; Yuniarti Anwar; Harby R Wiralaga (KOLEGIAL, 2023)
The purpose of this study was to determine the factors that influenced the demand for rail transportation services during the Covid-19 pandemic at Baturaja Station, Ogan Komering Ulu Regency. The method used in this research is descriptive method. The results showed that the relationship between all independent variables, namely price (X1), time (X2), and service (X3) to the dependent variable, namely service demand (Y) was strong. The coefficient of determination of R Square is 0.535 or 53.5%. This value indicates that the contribution of all independent variables, namely price (X1), time (X2), and service (X3), is 53.5% of the dependent variable service demand (Y). The tcount coefficient of the price variable (X1) is 2.972 where tcount > ttable (2.972 > 1.986) means that there is an effect of price (X1) on the demand for services (Y) for rail transport at the Baturaja station, Ogan Komering Ulu Regency. The tcount coefficient of the time variable (X2) is 0.688 where tcount < ttable (0.688 <1.986) means that there is no effect of time (X2) on the demand for services (Y) for rail transport at the Baturaja station, Ogan Komering Ulu Regency. The tcount coefficient of the service variable (X3) is 5.049 where tcount > ttable (5.049 > 1.986) means that there is an influence of service (X3) on the demand for services (Y) of rail transport at the Baturaja station, Ogan Komering Ulu Regency. The F test obtained the results of fcount > ftable which is equal to (35.682 > 2.70) this means that price (X1), time (X2), and service (X3) have an influence on the demand for services (Y) for rail transport at Baturaja station, Ogan Regency Komering Ulu.